(3GdMGTjI Ydi GdeYGdes - (3GdeGRfOQGfj, GdCUagGfj, MSGe GdOjf, eMeO UGdM Hf CMeO, J (B1081 (3g`s ((3MSjf Hf eMeO Jbjs)
(3ChdgG (B:s
(3fMeOc Gddge jG ef NdbfG hde fc TjFG ePchQG (B... (3bhdg GdMeO ddg, GddGe EeG ddLfS Gh ddGSJZQGb hYdi GdJbOjQjf jajO GNJUGU LfS GdMeO Hg SHMGfgs
(3BNQgG (B:s
(3BNQgG(B: (3hMcGjI eDef Bd aQYhf dCfG fbhd djSJ GdHdGZI (B.. (3hMSf GdJCdja aj GdeYfi Hd dGHO ajgG ef eQGYGI MSf GdJQcjH aj GdfXe CjkVG hfXe gPg GdbUU SfI SHMGfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B6: 151s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs